Portal Vein Pulsatility Index as a Potential Risk of Venous Congestion Assessed by Magnetic Resonance Imaging: A Prospective Study on Healthy Volunteers - Abou-Arab, Osama; Beyls, Christophe; Moussa, Mouhamed Djahoum; Huette, Pierre; Beaudelot, Elodie; Guilbart, Mathieu; De Broca, Bruno; Yzet, Thierry; Dupont, Hervé; Bouzerar, Roger; Mahjoub, Yazine (Frontiers in Physiology, 2022)
High values of portal vein pulsatility index (PI) have been associated with adverse outcomes in perioperative or critically ill patients. However, data on dynamic changes of PI related to fluid infusion are scarce. We aimed to determine of dynamic changes in PI is associated to fluid challenge (FC). To address this challenge, we conducted a prospective single-center study. The population study was healthy subjects. FC consisted in the administration of 500 ml of Ringer lactate infusion over 5 min. Portal blood flow and PI were assessed by magnetic resonance imaging. The responsiveness to FC was defined as an increase in cardiac stroke volume of at least 10% as assessed by echocardiography. We included 24 healthy volunteers. Fourteen (58%) subjects were responders and 10 (42%) were non-responders. In the responder group, FC induced a significant increase in portal blood flow from 881 [762-1001] at baseline to 1010 [778-1106] ml min-1 (p=0.005) whilst PI remained stable (from 31 [25-41] to 35 [25-42] %; p=0.12). In the non-responder group, portal blood flow remained stable after FC (from 1042 to 1034 ml min-1; p=0.084) whereas PI significantly increased from 32 [22-40] to 48 [25-85] % after FC (p=0.027). PI was negatively correlated to portal blood flow (Rho coefficient= -0.611; p=0.002). To conclude, PI might be a sensitive marker of early congestion in healthy subjects that did not respond to FC. This finding requires further validation in clinical setting with larger sample size.